Career in Obstetrics and Gynecology; to be or Not to be: A Study of Intern Doctors in a Nepalese Medical College - Aryal, Shreyashi; Shrestha, Deepak (Nepal Journal of Obstetrics and Gynaecology, 2019)
Aims: To find the preference of career in Obstetrics and Gynecology among interns at the end of internship and factors influencing this choice. Methods: A semistructured questionnaire was distributed to interns at the end of a one year rotatory internship. Demographic factors and clinical exposure in Obstetrics and Gynecology (ObGyn) were assessed using chi-square test and attitudinal factors were measured using 5 point Likerts scale. This was compared with interns choosing other subjects. Mean score on Likerts scale was compared with independent t-test. Logistic regression analysis was used to predict independent factors affecting career choice in ObGyn. Results: Out of 174 interns, 22 (12.6%) chose ObGyn as the first career choice. Female gender (OR=1.46), urban residence (OR=1.21) and having a doctor in the family (OR=1.22) were factors associated with choosing ObGyn. Social commitment (p=0.027), high income potential (p=0.000), focus on urgent care (p= 0.000), gratifying practice (p=0.043) and short postgraduate training (p=0.000) were attitudinal factors related to this choice. Conclusions: Though ObGyn is a popular choice, students tend to change minds against it throughout medical school, influenced by various experiences. Department of ObGyn has a major responsibility to develop role models and encouraging mentors so that students choose ObsGyn with interest and do not regret the choice till the end of medical school.